A real-world data analysis of tirzepatide in the FDA adverse event reporting system (FAERS) database - Liu, Liyuan (Frontiers in Pharmacology, 2024)
Background: Tirzepatide, a glucose-dependent insulinotropic polypeptide (GIP) receptor and glucagon-like peptide-1 (GLP-1) receptor agonist, is indicated for chronic weight management in adults with obesity or overweight as an adjunct to a reduced-calorie diet and increased physical activity. However, the safety profile of Tirzepatide-associated adverse events (AEs) requires comprehensive evaluation. Methods: The AE reports from the first quarter of 2022 to the third quarter of 2023 were selected by exploring the FDA Adverse Event Reporting System (FAERS) database. The new and unexpected potenial AE signals were detected using the disproportionality analysis, including reporting odds ratio(ROR), the proportional reporting ratio (PRR) the Bayesian confidence propagation neural network (BCPNN) and the empirical Bayes geometric mean(EBGM). Then the MedDRA was used to systematically classify the results. Results: A total of 1,904,481 case reports were obtained from 2022Q2 to 2023Q3. Forty-sixth tirzepatide-induced ADRs at the preferred terms (PTs) level are associated with 8 system organ class (SOCs). In addition, this study uncovered multiple anticipated ADRs, such as gastrooesophageal reflux disease, dyspepsia, and vomiting, in line with the drug labels. Moreover, unexpected and significant ADRs at PTs level, such as incorrect dose administered, injection site haemorrhage, and increased appetite, were discovered and linked to Injury, poisoning, and procedural complications, General disorders and administration site conditions, and Metabolism and nutrition disorders at the SOC level. Conclusion: This study offered new perspectives on the monitoring, surveillance, and management of adverse drug reactions related to tirzepatide. The outcomes of severe adverse events and their respective detection signals, along with unexpected significant adverse event signals, are important to consider in efforts to enhance clinical medication safety when using tirzepatide.